Spatially resolved tryptophan–kynurenine niches in HNSCC: immunometabolic microdomains and therapeutic implications - Ning, Wanchen; Huang, Shaohong (Frontiers in Immunology, 2026)
Head and neck squamous cell carcinoma (HNSCC) develops within a chronically inflamed tumor microenvironment (TME) where metabolic reprogramming and immune suppression tightly co-evolve. A prominent example is the tryptophan–kynurenine (Trp–Kyn) pathway, initiated by indoleamine 2,3-dioxygenase 1/2 (IDO1/IDO2) and tryptophan 2,3-dioxygenase (TDO2), which converts tryptophan into kynurenine and downstream metabolites that engage stress-response programs and aryl hydrocarbon receptor (AhR) signaling. In HNSCC, Trp–Kyn enzymes are inducible by interferons and oncogenic cues and are distributed across malignant cells as well as cancer-associated fibroblasts, endothelial cells and tumor-associated myeloid populations, generating spatially restricted “Trp-low/Kyn-high” immunometabolic niches. Within these niches, tryptophan starvation and kynurenine-driven signaling converge to suppress effector T-cell expansion, promote regulatory T-cell programs, undermine dendritic-cell priming and reinforce tolerogenic myeloid states, collectively fostering T-cell exhaustion and reduced sensitivity to PD-1/PD-L1 blockade. Emerging bulk, single-cell and spatial multi-omics studies support the idea that pathway activity is compartmentalized rather than uniform, providing a mechanistic rationale for the limited performance of first-generation IDO1 inhibitor strategies in unselected clinical settings. This mini-review synthesizes current evidence on Trp–Kyn microdomains in the HNSCC TME and discusses therapeutic opportunities that move beyond single-enzyme inhibition, including dual IDO1/TDO2 targeting, AhR antagonism and biomarker-guided combination regimens to restore antitumor immunity.